Linking the cell cycle to cell fate decisions - Dalton, Stephen (Trends Cell Biol, 2015)
Pluripotent stem cells retain the ability to differentiate into a wide-range of cell types while undergoing self-renewal. They also exhibit an unusual mode of cell cycle regulation, reflected by a cell cycle structure where G1- and G2-phases are truncated. When individual pluripotent stem cells are exposed to specification cues, they activate developmental programs and remodel the cell cycle so that the length of G1 and overall cell division times increase. The response of individual stem cells to pro-differentiation signals is strikingly heterogeneous, resulting in asynchronous differentiation. Recent evidence indicates that this phenomenon is due to cell cycle-dependent mechanisms that restrict the initial activation of developmental genes to the G1-phase. This suggests a broad biological mechanism where multipotent cells are ‘primed’ to initiate cell fate decisions during their transition through G1. Mechanisms underpinning commitment towards the differentiated state and its relationship to the cell cycle are discussed.